2010
DOI: 10.1016/j.phymed.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isoquinoline alkaloids from two Hippeastrum species on in vitro acetylcholinesterase activity

Abstract: The treatment of neurological disorders and neurodegenerative diseases is related to the levels of acetylcholine (ACh) through the inhibition of acetylcholinesterase (AChE). Galanthamine, an important alkaloid isolated from the Amaryllidaceae family, is approved for the pharmacological treatment of Alzheimer's disease (AD) and acts by inhibiting the acetylcholinesterase (AChE) activity. In the present study, Ellman's method was used to verify the inhibition of AChE activity of some isoquinolines alkaloids such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Several species in the Ipomoea family have been discovered to exhibit potent anticholinesterase activity in vitro such as the leaves of Ipomoea asarifolia 30 and Ipomoea aquatica Forsk 30 . In addition, isquinoline alkaloids isolated from Hippeastrum species demonstrated significant AChE inhibitory activity which also opens the possibility of the active component in I. muricata being an alkaloid 31 .…”
Section: Fig2: Ellman Esterase Assay Using Microplate Readermentioning
confidence: 91%
“…Several species in the Ipomoea family have been discovered to exhibit potent anticholinesterase activity in vitro such as the leaves of Ipomoea asarifolia 30 and Ipomoea aquatica Forsk 30 . In addition, isquinoline alkaloids isolated from Hippeastrum species demonstrated significant AChE inhibitory activity which also opens the possibility of the active component in I. muricata being an alkaloid 31 .…”
Section: Fig2: Ellman Esterase Assay Using Microplate Readermentioning
confidence: 91%
“…Galanthamine (purity [ 99 %) used for the calibration curves was previously obtained by the authors, and codeine (purity C 99 %) used as internal standard was purchased from Sigma Aldrich (St. Louis, MO, USA). (Castilhos et al 2007;da Silva 2005;da Silva et al 2008;Pagliosa et al 2010;Giordani et al 2011a, b;de Andrade et al 2011;Sebben 2005).…”
Section: Chemicalsmentioning
confidence: 99%
“…vittatum and R. bifida, in which elevated levels of montanine were detected, also exhibited notable AChE inhibitory effects (Table 2). Montanine (25) has previously demonstrated remarkable activity against AChE obtained from rat brain, with more than 50 % inhibition at 1 mM (Pagliosa et al 2010). These results, together with psychobiological activities reported earlier for montanine (da Silva et al 2006), reinforce the potential of montanine-type derivatives as therapeutic candidates for AChE inhibition or other functions related to the central nervous system (da Silva et al 2006;Pagliosa et al 2010).…”
Section: Ache Inhibitory Assay For Alkaloid-rich Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, harmine and numerous related β-carboline derivatives were found as potent and specific inhibitors of cyclin-dependent kinases (CDKs), and the structure activity relationships (SARs) analysis demonstrated that the degree of aromaticity www.intechopen.com (Jin, 2011;Pagliosa et al, 2010) (Muthumani et al, 2010;Ueda & Yamamura, 1999a, 1999b Mimosa tenuiflora (Fabaceae) Table 3. Aphrodisiacs plants and their alkaloids, xanthines and others amines of the tricyclic ring and the positioning of substituents were crucial for inhibitory activity.…”
Section: Alkaloids Xanthines and Others Aminesmentioning
confidence: 99%